The role of intra- and interpersonal relations in the process of diagnosis and treatment - Stanisławska-Kubiak, Maia; Warchoł-Biedermann, Katarzyna; Skommer, Maria; Mojs, Ewa; Wójciak, Rafał W. (Journal of Medical Science, 2019)
Introduction. There is an increasing tendency to adopt biopsychosocial approach to teaching how to care for patients. Participation in Balint’s groups is used to train students in communication and building relations with patients. Aim. To identify positive and negative aspects of participation in Balint’s groups, which are a part of compulsory training for students. Material and Methods. 70 medical students, who took part in the study, filled in a questionnaire specifically developed for students participating in Balint’s group. The questionnaire consisted of three open questions. The answers were collected and then analyzed by way of qualitative analysis of text and factorial analysis Results. The results suggest that Balint’s method can be difficult for medical students because they have not practiced building therapeutic relations with patients. Nevertheless, most students benefit from training in terms of personal development, awareness of mechanisms influencing patients — doctor communication and satisfaction with participation in classes. Conclusion. Balint’s Workshops is a useful method of teaching which influences medical student’s self — reflection because they become aware of the necessity of personality development.